40 Jahre Duales Studium Festschrift. - Werner, Jürgen (De Gruyter Oldenburg, 2015)
Celebrating "40 years of dual degrees," the Baden-Württemberg Cooperative State University has published a collection of 20 research papers from the field of economics. The essays cover themes ranging from happiness research to innovative business models.